Edukasi Media Tanam Hydrogel Untuk Siswa Sekolah Dasar di SD Negeri 1 Klakah, Kecamatan Selo, Kabupaten Boyolali - H, Nurlina (Program Studi Kehutanan, Universitas Khairun, 2024)
Public awareness about the importance of plants and their benefits is currently still low, both in the context of planting in gardens and in home gardens. Therefore, support and education are very necessary due to the lack of knowledge about alternative planting media other than soil. Education about landless farming to elementary school children can increase students' interest in the world of agriculture and hone their creativity. Hydrogel technology can be used as a solution as an indoor growing medium. Hydrogels are polymer crystals that are able to absorb and store large amounts of water and nutrients for plants. Hydrogel can also be decomposed naturally by microbes, making it safe to use. This service program is implemented through the Boyolali 6 Inspiration Class activities at SDN 1 Klakah, Selo District, Boyolali, Central Java. This service was aimed at elementary school children and was also witnessed by teachers at SDN 1 Klakah.